Technologies for Near-Field Focused Microwave Antennas. (19th March 2017) - Nepa, Paolo; Buffi, Alice; Michel, Andrea; Manara, Giuliano
Abstract : This paper provides a review spanning different technologies used to implement near-field focused antennas at the microwave frequency band up to a few tens of GHz: arrays of microstrip patches and printed dipoles, arrays of dielectric resonator antennas, reflectarrays, transmitarrays, Fresnel zone plate lenses, leaky-wave antennas, and waveguide arrays.